81.6k views
5 votes
What is the product?

(negative 3 s + 2 t)(4 s minus t)

negative 12 s squared minus 2 t squared
negative 12 s squared + 2 t squared
negative 12 s squared + 8 s t minus 2 t squared
negative 12 s squared + 11 s t minus 2 t squared

User Joe Flack
by
4.9k points

1 Answer

2 votes

Answer:


\boxed{- 12 {s}^(2) + 11st - 2 {t}^(2) }

Explanation:


= > ( - 3s + 2t)(4s - t) \\ \\ = > - 3s(4s - t) + 2t(4s - t) \\ \\ = > ( ( - 3s) * 4s )- (( - 3s) * t) + (2t * 4s) - (2t * t) \\ \\ = > - 12 {s}^(2) - ( - 3st) + 8st - 2 {t}^(2) \\ \\ = > -12 {s}^(2) + 3st + 8st - 2 {t}^(2) \\ \\ = > - 12 {s}^(2) + 11st - 2 {t}^(2)

User Marko Jurisic
by
4.3k points